HOTS-authentic Assessment Model Implementation of Tissue Structure Materials in High School of Malang: A pre-validation Final Draft - H. Husamah; Atok Miftachul Hudha; Zhangswe Ariandina Putri (IKIP Mataram, 2019)
Higher-Order Thinking Skills (HOTS) must be owned by students, and need to be assessed authentically. This study aimed to 1) analyze the efforts of high school teachers in Malang in developing a HOTS-authentic assessment in tissue structure materials; and 2) analyze the pre-validation final draft of the HOTS-authentic assessment model on tissue structure materials. The research method used was Research and Development (R&D). However, in line with the objectives, this publication only focuses on define, design, and develop. The developed part is only on the product (a pre-validation final draft). The research was carried out in state high schools in Malang (SSHS 1, 3, 4, 7, and 8). The study was conducted in April-November 2018. The subjects were 2 teachers from each school (10 teachers in total). Research data and findings were analyzed by descriptive-analytic qualitative. The results showed that teachers have included or considered HOTS aspects in lesson plans. However, the development of HOTS aspects and their assessment were not able to be carried out maximally. In practice, in a greater percentage, teachers use lesson plans without modification or making adjustments to student conditions. They modify and incorporate the HOTS aspect if there is an opportunity to discuss with other part who guide them. Therefore, the existence of this assessment model is very needed. The pre-validation final draft is essentially in the form of concepts that can be linked to the MGMP activities, and various related part, in an interactive and cyclical relationship (as a model for professional development of biology teachers).